UTILITY OF PAPERLESS PARTOGRAM IN LABOR MANAGEMENT - Choubisa, Pallavi; Chauhan, Madhubala; Rawal, Pramod; Kanwat, Babita; Singhal, Megha (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: To compare WHO-modified partograph and paperless partogram in the effective management of labor. Methods: A prospective analytical study was carried out in the Department of Obstetrics and Gynecology, Pannadhay Zanana Hospital at RNT Medical College, Udaipur. A sample of 400 pregnant women was recruited by random sampling from the labor room, for 1 year (June 01, 2021, to May 31, 2022). Women fulfilling inclusion criteria were randomly assigned for monitoring of labor in an active phase of labor ≥ 4 cm of cervical dilatation. Results: The mean age was 26.46 ± 3.90 years with an age range of 18–37 years, 65% were rural. 11% crossed alert line and 1.5% crossed action line. 94.75% had a normal vaginal delivery and 21 (5.25%) cases had lower segment cesarean section (LSCS). As indication for LSCS 16 (76.19%) had fetal distress and 5 (23.81%) had secondary arrest of dilatation and descent head. 17 (4.25%) had APGAR <7 at 5 min and no stillbirth was reported. Conclusion: We concluded that the paperless partogram was effective and user-friendly in the management of labor and prevention of abnormal or prolonged labor when compared to the WHO partogram in low-risk cases.